2022
DOI: 10.1177/1759720x221080377
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biologic agents for the treatment of osteoarthritis: a meta-analysis of randomized placebo-controlled trials

Abstract: Background: We aimed to evaluate the efficacy and safety of biologic agents targeting three main cytokines, that is, nerve growth factor (NGF), interleukin-1 (IL-1), and tumor necrosis factor-α (TNF-α), for osteoarthritis (OA) treatment. Methods: Databases (PubMed, Embase, and Cochrane Library) and ClinicalTrials.gov were systematically searched for randomized placebo-controlled trials (RCTs) of biologic agents from inception to November 15, 2020. The outcomes were the mean change in pain, function scores, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 90 publications
(113 reference statements)
1
6
0
1
Order By: Relevance
“…To update the anti-IL-1 therapeutic evidence in the treatment of KOA, we included 12 RCTs covering three anti-IL-1 therapeutic categories based on the mechanism of action: ABT981, AMH108, and canakinumab were reported in four studies as IL-1 antibodies [51,55,57,58]; Orthokine and Anakinra were reported in four studies as IL-1 Ras [52][53][54]56]; and diacerein was reported in four studies as an IL-1 inhibitor [59][60][61][62]. Compared with previous studies that were either narrative reviews or meta-analyses involving only some anti-IL-1 therapeutics [46][47][48], the present work comprehensively evaluated the efficacy and safety of the three main anti-IL-1 therapeutics, including IL-1 antibodies, IL-1 Ras, and an IL-1 inhibitor. Considering The antagonism of IL-1 in the treatment of OA as well as the potential pathways has been continuously discovered [63][64][65].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To update the anti-IL-1 therapeutic evidence in the treatment of KOA, we included 12 RCTs covering three anti-IL-1 therapeutic categories based on the mechanism of action: ABT981, AMH108, and canakinumab were reported in four studies as IL-1 antibodies [51,55,57,58]; Orthokine and Anakinra were reported in four studies as IL-1 Ras [52][53][54]56]; and diacerein was reported in four studies as an IL-1 inhibitor [59][60][61][62]. Compared with previous studies that were either narrative reviews or meta-analyses involving only some anti-IL-1 therapeutics [46][47][48], the present work comprehensively evaluated the efficacy and safety of the three main anti-IL-1 therapeutics, including IL-1 antibodies, IL-1 Ras, and an IL-1 inhibitor. Considering The antagonism of IL-1 in the treatment of OA as well as the potential pathways has been continuously discovered [63][64][65].…”
Section: Discussionmentioning
confidence: 96%
“…The current anti-IL-1 therapeutics found in the available literature for KOA mainly consist of the following three types: IL-1 antibodies, IL-1 Ras, and IL-1 inhibitors [39][40][41][42][43][44][45]. The literature included in the current published meta-analysis is not comprehensive, as some drugs are missing or the latest research results are missing as they were not available at the time of publication, so the inconsistent efficacy and safety of anti-IL-1 therapeutics in KOA reported in the literature cannot comprehensively explain the advantages and disadvantages of anti-IL-1 therapeutics [46][47][48]. Therefore, the correct clinical treatment strategy may not be made by solely relying on the results of existing studies and there is a need to update the data on the efficacy and safety of anti-IL-1 therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the heterogeneity of OA phenotypes and the complexity of the interaction of pro-inflammatory signaling pathways [ 49 , 50 ]. Current meta-analyses found that although biologic agents were generally effective for OA pain relief, subgroup of IL-1 inhibitors or TNF-α inhibitors were not superior to placebo [ 10 , 11 , 12 ]. We demonstrated consistent results on the ineffectiveness of IL-1 inhibitors, but inconsistently we found infliximab could be effective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fleischmann et al [ 8 ] suggested that lutikizumab use significantly relieved pain compared with placebo, while Kloppenburh et al [ 9 ] reported that lutikizumab did not alleviate pain or imaging outcomes in comparison to placebo. Moreover, previous systematic reviews also indicated the inconsistent efficacy of biologic agents [ 10 , 11 , 12 ]. Therefore, we performed an up-to-date network meta-analysis to compare the efficacy and safety of biologics targeting inflammation among OA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Внедрение анакинры в клиническую практику началось с 2001 года, когда препарат был зарегистрирован для лечения ревматоидного артрита (РА), а в дальнейшем -криопирин-ассоциированных периодических синдромов и синдрома DIRA (Defi ciency of Interleukin 1 Receptor Antagonist), связанного с дефицитом синтеза ИЛ-1Ra. C момента регистрации и по настоящее время время накапливаются данные, касающиеся применения анакинры по незарегистрированным (off label) показаниям для лечения широкого круга САВЗ и гипервоспалительных синдромов, в патогенезе которых предполагается участие аутовоспалительных механизмов [24][25][26] Артрит, вызванный кристаллами гидроксиапатита Наблюдательные исследования [117,118] Анкилозирующий спондилит Открытое наблюдательное исследование [119] Псориатический артрит Открытое проспективное исследование [120] Остеоартрит РПКИ (в/с) [121], клинические случаи [122,123], метаанализ [124]; эффект отсутствует…”
Section: применение анакинры при ивзunclassified